2019
DOI: 10.1055/s-0039-3400954
|View full text |Cite
|
Sign up to set email alerts
|

The Olerud Extensile Anterior Approach for Complex Distal Femoral Fractures: A Systematic Review

Abstract: The management of AO/OTA (AO Foundation/Orthopaedic Trauma Association) 33-C3 complex distal femoral fractures presents challenges for orthopaedic surgeons. The extensile anterior approach may be an appropriate alternative treatment technique. The purpose of this systematic review is to (1) evaluate the Olerud approach (extensile anterior approach) for the treatment of 33-C3 complex distal femoral fractures and (2) evaluate postoperative patient outcomes. A systematic literature search was performed to retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The Olerud approach (extensile anterior approach with tibial tuberosity osteotomy) in a recent systematic review was shown to have good/excellent functional outcomes in 57% of patients. 8 Swashbuckler approach was described by Starr et al as a modified anterior approach to the distal femur, that facilitated complete exposure of distal femur articular surface and provided quicker rehabilitation. 9 The anterior skin incision utilized for the approach would not compromise the future skin incisions necessary for total knee replacements.…”
Section: Introductionmentioning
confidence: 99%
“…The Olerud approach (extensile anterior approach with tibial tuberosity osteotomy) in a recent systematic review was shown to have good/excellent functional outcomes in 57% of patients. 8 Swashbuckler approach was described by Starr et al as a modified anterior approach to the distal femur, that facilitated complete exposure of distal femur articular surface and provided quicker rehabilitation. 9 The anterior skin incision utilized for the approach would not compromise the future skin incisions necessary for total knee replacements.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis of the ankle joint is characterised by the progressive degeneration of articular cartilage and accounts for approximately 2% of all cases [17]. It often presents with chronic ankle pain, physical deformity, and reduced range of motion [22,28]. Approximately 70% of cases are associated with a traumatic aetiology [27].…”
Section: Introductionmentioning
confidence: 99%